ANALISIS KEBUTUHAN PENGEMBANGAN BAHAN AJAR BERBASIS E-BOOK INTERKATIF PADA PEMBELAJARAN IPAS KELAS V SEKOLAH DASAR - Bariroh; Erni Suharini; Hamdan Tri Atmaja (STKIP Subang, 2024)
The use of teaching materials in learning IPAS in primary schools greatly affects the learning motivation of students. In IPAS learning, interactive teaching materials are needed so that students are motivated and active in the learning process. The purpose of this study was to analyse the need for interactive teaching materials in supporting IPAS learning activities. The research method used is a qualitative method, focusing on the description of the analysis of teacher needs, the needs of students regarding the teaching materials needed in IPAS learning, and the analysis of school facilities as a means of supporting learning. The necessary data were obtained through interviews, questionnaires with students and fifth grade teachers, and observation of facilities at SD Negeri Slerok 6 Tegal City. The pre-survey data showed that the lack of innovation in the selection of teaching materials used by teachers during the learning process contributed to the low motivation of students. From the needs analysis of teaching materials conducted by researchers, it was found that both teachers and students need teaching materials that are more interactive and technology-based. Interactive e-book-based teaching materials are an option for use in learning grade V IPAS material